State land control in the Republic of Kazakhstan: problems of legal regulation - Jabaildayeva, Gulnar T. (Journal of the Belarusian State University. Law, 2019)
The state control in the field of land use and protection is investigated as a function of state regulation and management in the field of land use and protection according to the legislation of the Republic of Kazakhstan. The ratio of state land and environmental control is analyzed, the conclusion is made that state land control is an integral part of general environmental control and should be based on common principles of environmental control. Proposals are made to improve environmental and land legislation, recommendations on streamlining the institutional structure of environmental control activities, including the proposal to establish an environmental monitoring body under the President of the Republic of Kazakhstan.
Keywords: state environmental control; land control; land protection; authorized state bodies; officials; local executive bodies; spheres of control activity; list of state bodies; subjects of control